Experimental evolution under hyper-promiscuity in Drosophila melanogaster. Issue 1 (December 2016) - Perry, Jennifer; Joag, Richa; Hosken, David; Wedell, Nina; Radwan, Jacek; Wigby, Stuart
Abstract Background The number of partners that individuals mate with over their lifetime is a defining feature of mating systems, and variation in mate number is thought to be a major driver of sexual evolution. Although previous research has investigated the evolutionary consequences of reductions in the number of mates, we know little about the costs and benefits of increased numbers of mates. Here, we use a genetic manipulation of mating frequency inDrosophila melanogaster to create a novel, highly promiscuous mating system. We generatedD. melanogaster populations in which flies were deficient for the sex peptide receptor (SPR ) gene – resulting inSPR- females that mated more frequently – and genetically-matched control populations, and allowed them to evolve for 55 generations. At several time-points during this experimental evolution, we assayed behavioural, morphological and transcriptional reproductive phenotypes expected to evolve in response to increased population mating frequencies. Results We found that males from the high mating frequencySPR - populations evolved decreased ability to inhibit the receptivity of their mates and decreased copulation duration, in line with predictions of decreased per-mating investment with increased sperm competition. Unexpectedly, SPR- population males also evolved weakly increased sex peptide (SP ) gene expression. Males fromSPR- populations initially (i.e., before experimental evolution) exhibited more frequent courtship and faster time until mating relative to controls, but over evolutionary time these differences diminished or reversed. Conclusions In response to experimentally increased mating frequency, SPR- males evolved behavioural responses consistent with decreased male post-copulatory investment at each mating and decreased overall pre-copulatory performance. The trend towards increased SP gene expression might plausibly relate to functional differences in the two domains of the SP protein. Our study highlights the utility of genetic manipulations of animal social and sexual environments coupled with experimental evolution.